Business Saving and Errors in Variables - Hart, P. E. (Review of Economic Studies, 1965)
Journal Article Business Saving and Errors in Variables Get access P. E. Hart P. E. Hart University of Bristol Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 3, July 1965, Pages 225–232, https://doi.org/10.2307/2295826 Published: 01 July 1965